Effects of policy changes on agricultural practices related to selected crops in Malaysia - Gafurjanovich, Abdulla Ibragimov (2014)
The agricultural sector growth in Malaysia may not be sustainable in the future as agriculture and food sectors are continuously challenged by shifting fundamentals, resource constraints and climate change. The “business as usual” stance for agriculture may be detrimental to Malaysia in terms of opportunity cost, inefficient use of resources, food insecurity and outflow of foreign exchange for imports. The Malaysian agriculture is biased towards industrial crops, such as palm oil, rubber and cocoa. As in 2015, palm oil accounted for about 4% of the gross domestic product (GDP) and 0.53% for rubber. The share of industrial crops in the land use has increased from 68.5% in 1960 to over 80% in 2015. On the other hand, the land use for the food crops shows an opposite trend. If this trend persists, the food security of the country may be affected. The agriculture is beset with a number of development issues which remain unaddressed despite the rapid industrialization. These include sectoral division between the industrial crops (palm oil and rubber) and the food commodities (fruits and vegetables, livestock and fisheries). While industrial crops are continuously supported by the government, the food sector is largely marginalized with the exception of paddy and rice sector. Within these sectors, there is another dichotomy between the estates and the smallholders with a significant gap in terms of productivity and returns. Due to higher returns in the palm oil industry, the returns in the rubber and cocoa industries have shrunk significantly (production and area) with most of the farms run by the smallholders i.e. 95% in the rubber and 95% in cocoa sectors). The big gap between the estates and smallholders clearly indicates poor technology transfer and coordination, which calls for improvement in technology transfer, structural and institutional readjustments. Towards these ends, the study has adopted the system dynamics methodology to capture the circular causality between variables in the crop production system as well as delays and non-linearities. The general objective of the study is to identify the key policy interventions towards revitalization of the agriculture sector with respect to primary production growth, equity and sustainability. The specific objectives are: (i) To determine structural and institutional factors that lead to the crop mix shift and slow growth in production; (ii) To determine structural and institutional factors that lead to the low income to the farmers and their uncertain livelihoods; (iii) To develop a system dynamics model to capture causal relationship between major structural elements in the sector that lead to the overall poor performance; (iv) To identify the key policy interventions to revitalize and sustain the agriculture sector with respect to primary production growth, equity and sustainability based on the developed system dynamics model. The findings indicate that funding for R&D for development of high yielding varieties, gradual transition to automation and mechanization, local input production along with accelerated replanting hold big promise towards productivity enhancement, cost reduction, thus, higher return particularly to the smallholders. These in turn result in an equitable income distribution among participants both in the industrial and food crop sectors which contributes to an optimal mix of crops and sustainability of the agriculture sector at large.